Le elezioni amministrative del 2014 a Perugia: la fine di un sistema politico locale. Un confronto con il caso di Livorno - Maurizio Ribechini (QOE-IJES)
The Italian local election held in spring 2014 resulted in a surprising political landscape. In particular, in the Umbrian town of Perugia, where for the first time in history, the centre-left coalition has lost the political leadership of the city, after having administered for almost seventy years after the end of World War II. In Umbrian capital in fact the mayoral candidate of the Democratic Party was defeated after the second round by the candidate of the centre-right coalition. This article tries to shed lights on the reasons behind this political change. More specifically, the article looks at the electoral results of 2014, 2009 and 2004; moreover, it is based on interviews to politicians and observers. After this analysis, a comparison with the case of the 2014 municipal elections of Livorno will be provided. As a conclusion, the article tries to understand if the political changes experienced by both Perugia and Livorno can be a signal of a big transformation of local power and if they can also be extended to other territories.